Manifestations of Slang in Improving Informal Subvariety ofThe Indonesian Language - Neina, Qurrota Ayu; Tran Thi Khanh Vi (Jurnal Sastra Indonesia, 2025)
Slang is a unique phenomenon in society. Related to this phenomenon, slang is a language commonly used by the community, often with modified vocabulary. Slang is an increasingly prevalent social phenomenon among young people today. Based on previous research, several factors have triggered its resurgence among young people. Related to this, this article will discuss the manifestation of slang as one of the informal subvarieties in Indonesia. The use of slang is recommended to be able to develop in a society with several considerations, including (a) Slang is just one subvariety of Indonesian; (b) Slang increases the expressive power and diversity of Indonesian; (c) Slang indicates cultural pluralism in Indonesian; (d) Slang is just a variant form of the informal variety of Indonesian. Thus, slang and its use cannot be considered vulgar.